2021
DOI: 10.3390/biology10121302
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Predicted Functional Diversities of Bacterial Microbiome in Response to Sewage Sludge Amendment in Coastal Mudflat Soil

Abstract: The study investigated the influence of sewage sludge application at rates of 0 (CK), 30 (ST), 75 (MT), and 150 (HT) t ha−1 to mudflats on bacterial community diversity and predicted functions using amplicon-based sequencing. Soils under sewage sludge treatments, especially the HT treatment, exhibited lower pH, salinity and higher nutrient contents (C, N, and P). Moreover, restructured bacterial communities with significantly higher diversities and distinct core and unique microbiomes were observed in all sewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 113 publications
2
10
0
Order By: Relevance
“…More bacteria in the EI group suggest that bacteria may play a key role in promoting N metabolism in the rhizosphere (Hacquard et al, 2015; Näsholm et al, 2009). This process, in turn, may increase the plant nutrient supply (Li, Wang, et al, 2021; Zhao et al, 2016). Although N application altered soil fertility, only the Chao1 index was significantly altered by N; the structural compositions at the bacterial phylum and genus levels did not differ significantly (Tables S2 and S3).…”
Section: Discussionmentioning
confidence: 99%
“…More bacteria in the EI group suggest that bacteria may play a key role in promoting N metabolism in the rhizosphere (Hacquard et al, 2015; Näsholm et al, 2009). This process, in turn, may increase the plant nutrient supply (Li, Wang, et al, 2021; Zhao et al, 2016). Although N application altered soil fertility, only the Chao1 index was significantly altered by N; the structural compositions at the bacterial phylum and genus levels did not differ significantly (Tables S2 and S3).…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to the improvement of soil macroaggregates by exogenous organic inputs in saline‐sodic soils, such as sewage sludge, manure, and vermicompost amendments (Bai, Zuo, et al, 2018; Hanay et al, 2004). Sewage sludge‐induced amelioration of soil chemical properties (i.e., pH, salinity, and SOC) and shift of soil microbial community diversity (especially the fungal microbiome) might be most responsible for the improvement of soil aggregation, as they have been widely demonstrated to be pivotal factors involved in soil aggregate formation (Li et al, 2021; Xiao et al, 2020). Additionally, enhanced aggregate stability with higher MWD and GMD but lower fractal dimension D and erodibility K were observed in the sludge‐amended saline soil (Figure 1b–e).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of soil pH and salinity, lower values were observed in reclaimed coastal saline soils, which was in accordance with previous literature that found that sewage sludge can efficiently alleviate the saline‐sodic condition in coastal areas (Bai et al, 2017). Compared with CK (8.91), lower pH values in LT (8.59), MT (8.53), and HT (8.28) soils (Table 1) were partially explained by the neutralization caused by sewage sludge with a lower pH (Table S1) and acid compounds derived from OM‐rich sewage sludge degradation (Li et al, 2021), while significantly improved soil aggregation status might be the primary reason for blocking the capillary rise of upward‐moving salt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations